Parallel Struggles of Religious Moderation Activists Amid Hindu-Muslim Tensions in India and Political Polarization in Indonesia - Parinduri, M. Azmi Alkhosyi Parinduri (Social Impact Journal, 2025)
The phenomenon of religious and political polarization has created serious pressure on religious moderation work, both in India and Indonesia. In India, interfaith activists who strive to maintain harmony between Hindu and Muslim communities often face stigmatization, labeling themselves as "anti-national," and pressure from the politically dominant majority group. Meanwhile, in Indonesia, religious moderation activists also experience high social and psychological burdens, especially after the 2024 election which was colored by identity sentiment and religious-based disinformation. This article attempts to comparatively review the forms of burnout experienced by moderation activists in both countries, and explain the patterns of structural, digital, and cultural pressures that make tolerance work increasingly vulnerable and marginalized. Through a qualitative approach with literature studies, this article shows that the struggle of moderation activists is not only about defending diversity, but also about surviving amidst increasingly extreme identity politics. These findings invite readers to understand that religious moderation requires social protection, policy support, and strengthening of a healthy digital space to prevent systemic fatigue that can endanger democracy itself.